Answer:
Number one: Infinite solutions
Number two: No solutions
Number three: X=6
Step-by-step explanation:
Number one:
10+6x=2(5+3x)
10+6x=(2)(5)+(2)(3x)(Distribute)
10+6x=10+6x
6x+10=6x+10
Step 2: Subtract 6x from both sides.
6x+10β6x=6x+10β6x
10=10
Step 3: Subtract 10 from both sides.
10β10=10β10
0=0
Number two:
Step 1: Simplify both sides of the equation.
3x+5βx=2x+7
3x+5+βx=2x+7
(3x+βx)+(5)=2x+7(Combine Like Terms)
2x+5=2x+7
2x+5=2x+7
Step 2: Subtract 2x from both sides.
2x+5β2x=2x+7β2x
5=7
Step 3: Subtract 5 from both sides.
5β5=7β5
0=2
Number three:
Step 1: Subtract 2x from both sides.
4xβ4β2x=2x+8β2x
2xβ4=8
Step 2: Add 4 to both sides.
2xβ4+4=8+4
2x=12
Step 3: Divide both sides by 2.
2x2=122
x=6